The Wildwood Bakery - Elliott, Rebecca (Elliott, Rebecca. Owl diaries, 2017)
Macy's little sister has wings that are too small, so Eva's class decides to raise money to buy her a flying chair, and half the class opens a bakery, and the other half opens a candy store--but soon competition between the two stores becomes more important than their goal, and Eva needs to convince the other owls that they will collect more money if everyone works as a team.